Effects of quarantine in imperfect disease control - Yang, Jiongcheng (2018)
The Ebola epidemic broke out in 2014 was one of the most influential disease in recent years. The epidemic was so serious that many countries are infected, mainly in West Africa. At the same time, some similar symptoms are also observed in other areas all over the world. In this project, to find the regular pattern of the spreading and quarantine, we build a scale-free network to simulate based on the previous studies. After that we do some analysis to the model and find the optimal control. In the first part, when considering the control strategies, we use SIR type model to understand the dynamics. Perfect control and imperfect control are both analyzed in this project. In the second part we discuss the stability of equilibrium based on the scale-free network and come up with the single strategy and global strategy of imperfect control. Finally, we apply mathematical analysis and numerical simulations to evaluate the result of different level of vaccination. Optimal control is raised and compared with the simulation result, and can be used for reference in practical control.